2010
DOI: 10.1029/2009jb007038
|View full text |Cite
|
Sign up to set email alerts
|

High‐speed friction of disaggregated ultracataclasite in rotary shear: Characterization of frictional heating, mechanical behavior, and microstructure evolution

Abstract: [1] To understand the frictional behavior of natural faults at seismic slip rates, high-speed rotary shear experiments were conducted on disaggregated ultracataclasite from the Punchbowl fault. The experimental gouge layers were sheared at normal stresses of 0.2-1.3 MPa and velocities of 0.1-1.3 m/s to total displacements of 1.3-84 m. We employ thermomechanical FEM models and microstructural observations to consider spatial and temporal variation of normal stress and temperature in the samples and understand m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
131
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(144 citation statements)
references
References 41 publications
(106 reference statements)
12
131
1
Order By: Relevance
“…In fact, high-velocity (1.3 m/s) friction experiments on natural fault gouges successively reproduced fluidization-related microstructures found in nature, during which the apparent coefficient of friction (ratio of shear to normal stress) decreased to approximately 0.1 to 0.2 (Mizoguchi et al 2009;Kitajima et al 2010;Ujiie and Tsutsumi 2010). Mizoguchi et al (2009) reported folding and fluttering structures in the gouge after high-velocity friction experiments under dry (room humidity) conditions.…”
Section: Fluidizationmentioning
confidence: 96%
“…In fact, high-velocity (1.3 m/s) friction experiments on natural fault gouges successively reproduced fluidization-related microstructures found in nature, during which the apparent coefficient of friction (ratio of shear to normal stress) decreased to approximately 0.1 to 0.2 (Mizoguchi et al 2009;Kitajima et al 2010;Ujiie and Tsutsumi 2010). Mizoguchi et al (2009) reported folding and fluttering structures in the gouge after high-velocity friction experiments under dry (room humidity) conditions.…”
Section: Fluidizationmentioning
confidence: 96%
“…Moreover, the differential speed across the sample affects the thermal evolution of the slipping zone: at the sample edge, where the slip rate is higher, the temperature increases faster than at the sample center. This results in uneven thermal dilatancy and normal stress distribution of the specimens, which affects the measured friction (e.g., Kitajima et al 2010). It follows that the utilization of larger in size and ring-shaped samples will yield more accurate experimental data.…”
Section: Friction Experiments and Earthquake Mechanicsmentioning
confidence: 99%
“…Although the breakdown of carbonates requires temperatures in excess of 800°C, similar dehydration reactions are likely to occur in some phyllosilicates at more modest temperatures of 150-200°C. These dehydration reactions have been proposed as a weakening mechanism in high-speed rotary shearing experiments of disaggregated ultracataclasite from the Punchbowl fault in Southern California (KITAJIMA et al 2010). In that study, slip velocities ranged from 0.1 to 1.3 m/s at normal stresses between 0.2 and 1.5 MPa and total displacements of 1.5-84 m. They reported a significant reduction in the coefficient of sliding friction when the slip velocity and normal stress were sufficiently high to generate calculated temperatures in excess of about 150°C.…”
Section: Introductionmentioning
confidence: 99%
“…In microstructural studies of radial sections from their deformed samples, KITAJIMA et al (2010) identified four distinct structural units. The first, a compacted, slightly sheared and modified starting material, and the second, a well-foliated and sheared gouge, were similar to those observed in other lowspeed experiments that produce friction coefficients near 0.6.…”
Section: Introductionmentioning
confidence: 99%